2010
DOI: 10.1200/jco.2009.23.3429
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Stem-Cell Transplantation in Patients With Hematologic Malignancies After Dose-Escalated Treosulfan/Fludarabine Conditioning

Abstract: Treosulfan-based conditioning was feasible at all three doses. The 3 x 14 g/m(2) dose was selected for additional studies, because it combines desired characteristics of low toxicity and a low relapse rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
81
4
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 38 publications
10
81
4
3
Order By: Relevance
“…FT was associated with rapid achievement of full donor chimerism, similar to FB4 and to MAC regimens, while the kinetics of engraftment of FB2 is more consistent with RIC/ NMA. Prior studies have documented a safe toxicity profile of FT. 8,16,22,23 In this study, severe mucositis was less often seen after FT, but the incidence of other organ toxicities was similar after the various regimens. The day of onset of neutropenia was significantly earlier after FT, consistent with the activity of treosulfan against both committed and non-committed stem cells, while BU spares committed stem cells.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…FT was associated with rapid achievement of full donor chimerism, similar to FB4 and to MAC regimens, while the kinetics of engraftment of FB2 is more consistent with RIC/ NMA. Prior studies have documented a safe toxicity profile of FT. 8,16,22,23 In this study, severe mucositis was less often seen after FT, but the incidence of other organ toxicities was similar after the various regimens. The day of onset of neutropenia was significantly earlier after FT, consistent with the activity of treosulfan against both committed and non-committed stem cells, while BU spares committed stem cells.…”
Section: Discussionmentioning
confidence: 72%
“…These differences were not statistically significant. Casper et al 16 reported NRM of 13% at day 100 and 20% at 2 years in their FT study. NRM did not increase with treosulfan dose between the 10 g/m 2 Â 3 level and 14 g/m 2 Â 3 dose level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…daily over 30 min from days À6 to À2). [39][40][41][42][43][44][45][46] For patients with unrelated donors, antithymocyte globulin (for example, ATG Fresenius, Fresenius Biotech, Munich, Germany (5-10 mg/kg)) was given i.v. daily from days À3 to À1.…”
Section: Regimensmentioning
confidence: 99%
“…High-dose treosulfan and fludarabine before allogeneic transplantation has shown efficacy with little toxicity in AML and myelodysplastic syndromes. 10,11 Treosulfan has also been investigated as a high-dose therapy before auto-SCT in ovarian cancer and other solid tumors. 12,13 A previous study demonstrated its activity in a high-dose combination regimen for relapsed aggressive lymphoma, 14 thereby expanding the limited number of high-dose protocols.…”
Section: Introductionmentioning
confidence: 99%